25(OH)-Vitamin D alleviates neonatal infectious pneumonia via regulating TGFβ-mediated nuclear translocation mechanism of YAP/TAZ. Issue 1 (1st January 2021) - Sun, Qi; Gao, Yiwen; Qiao, Lina; Yuan, Yi; Liu, Qian
ABSTRACT: Neonatal infectious pneumonia (NIP) is a common infectious disease that develops in the neonatal period. The purpose of our study was to explore the potential roles of 25(OH)-Vitamin D (25-OH-VD) and its anti-inflammatory mechanism in NIP. The results showed that serum 25-OH-VD level was negatively correlated with the severity of NIP, whereas Spearman's correlation analysis showed a significant positive correlation between the severity of NIP and the levels of pneumonia markers procalcitonin (PCT) and interleukin-6 (IL-6). The expression of vitamin D receptor (VDR) was down-regulated, while the transforming growth factor β (TGFβ), nuclear YAP, and TAZ were up-regulated in the peripheral blood mononuclear cells (PBMCs) of neonates with severe pneumonia. Neonates with 25-OH-VD deficiency were associated with an increased risk of NIP. In BEAS-2B cells, down-regulation of nuclear YAP and TAZ was found in the lipopolysaccharide (LPS) + VD group relative to the LPS-induced group. Additionally, positive rate of nuclear YAP, as detected by immunocytochemistry (ICC), and the nuclear translocation of nuclear YAP/TAZ by IFA in the LPS+VD group showed an intermediate level between that of the control and LPS-induced groups. Furthermore, the expressions of VDR and CYP27B1 were significantly increased in the LPS+VD group as compared to those in the LPS-induced group. The anti-inflammatory mechanism in NIP was achieved due to the 25-OH-VD mediating TGFβ/YAP/TAZ pathway, which suggested that using 25-OH-VD might be a potential strategy for NIP treatment.